Efforts to Eradicate Alcohol In the City of Gorontalo: A Study of the Principles of Adat Philosophy based on Sara, Sara based on Kita Bullah - Saharuddin Saharuddin; Ilham Ilham; Yeti S Hasan; Rusmulyadi Rusmulyadi; Albert Pede (Jurnal Hukum Volkgeist, 2022)
In 2020, as a form of government concern for the high circulation of alcoholic beverages (Miras) in the Serambi Medina area, the Regional People's Representative Council (DPRD) of Gorontalo Province continues to revise the Regional Regulation on Alcoholic Beverages (Perda), which was previously Perda Number 16 of 2015 (concerning the Supervision and Control of Distribution of Alcoholic Drinks). Which is considered not strong enough to stem the circulation of liquor. The results of a 2018 study by the Ministry of Health's Ministry of Health (Kemenkes) research, alcohol consumption in Gorontalo is ranked fourth nationally, only losing to North Sulawesi, East Nusa Tenggara and Bali. The purpose of this study is to see that efforts to eradicate liquor in Gorontalo City are not in accordance with Adat Principles. The novelty of this research helps provide input for local governments to perfect the draft local regulation on controlling liquor in Gorontalo City.